Structural and Optical Properties of CdTe Thin Films Deposited Using RF Magnetron Sputtering. (March 2017) - Kulkarni, Rupali; Rondiya, Sachin; Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Jadkar, Vijaya; Bhorde, Ajinkya; Date, Abhijit; Pathan, Habib; Jadkar, Sandesh
Abstract: In this work, we have studied the influence of RF power on structural and optical properties of CdTe thin films deposited by indigenously designed locally fabricated RF magnetron sputtering. Films were analyzed by using variety of techniques such as low angle X- ray diffraction, UV-Visible spectroscopy, Raman spectroscopy etc. to study its structural and optical properties. Low angle XRD analysis showed that CdTe films are polycrystalline and has cubic structure with preferred orientation in (111) direction. Raman scattering studies revealed the presence of CdTephase over the entire range of RF power studied. The UV-Visible spectroscopy analysis showed that the band gap decreases with increase in RF power. However, CdTe films deposited at higher RF power has optimum band gap values (1.44-1.60 eV). Such optimum band gap CdTe can be use as absorber material in CdS/CdTe and ZnO/CdTe solar cells.